Counseling international students: implications of the relationship between religious commitment and psychological adjustment - Ssekamanya, Siraje Abdallah (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2016)
Globalization and the internationalization of higher education have led to the increase of the number of students studying in foreign countries. Countries like Malaysia are hosting hundreds of thousands of international students every year. There are issues of cross-cultural adjustment faced by these students which, if not properly handled, may create problems for the students at their host institutions. Considering that religious atmosphere is one of the strengths presented by countries like Malaysia and Indonesia for attracting Muslim students from OIC member countries, it is interesting to explore the interplay of religious beliefs and practices and the psycho-educational adjustment of Muslim students in these countries. This paper is part of a larger study that sought to analyze the relationship between religious commitment and the degree of cross-cultural adjustment problems among international students in Malaysia. Data were collected from 118 students (males=94 & females=31), originating from 38 countries around the world. The instruments used for data collection included the Student Adaptation to College Questionnaire (Baker & Siryk, 1989), College Adjustment Scales (CAS) by Anton and Reed (1991), and a self-constructed Islamic Religious Commitment Questionnaire. It was found that religious beliefs and practices were positively correlated with positive aspects of adjustment, but negatively correlated with indicators of distress. Implications for counselling international students in a way that capitalizes on their religious beliefs and practices are discussed.